Home Physical Exercise Protocol for Older Adults, Applied Remotely During the COVID-19 Pandemic: Protocol for Randomized and Controlled Trial - D’Oliveira, Anderson; De Souza, Loiane Cristina; Langiano, Elisa; Falese, Lavinia; Diotaiuti, Pierluigi; Vilarino, Guilherme Torres; Andrade, Alexandro (Frontiers in Psychology, 2022)
The emergence of the new coronavirus (COVID-19) at the beginning of 2020, considered a public health emergency due to its high transmission rate and lack of specific treatment, led many countries to adhere to social isolation. Although necessary, social isolation causes important psychological changes, negatively affecting the health of the population, including the older population. The aim of this study is to propose a 4-week, home-based physical exercise protocol for older people in social isolation and evaluate whether will promote positive changes in psychological variables such as anxiety, mood, depression, and stress, and in the variables sleep, quality of life, and physical capacities in the older adults. The sample will be selected in a probabilistic way from individuals aged 60 years or more from the city of Itajaí (Santa Catarina, Brazil). Of these, half will perform a home-based resistance training protocol, with 3 weekly sessions, for 4 consecutive weeks. Outcomes will be depressive symptoms, sleep quality, quality of life, stress, mood states, anxiety, and functional capacity, evaluated at baseline, after 4 weeks, and after 15 days of follow-up. This study will offer a home-based exercise protocol for older adults, with load progression and remote monitoring, thus filling a gap in the provision of PE in this population. The results will be able to identify possible improvements not only in physical health, but also in quality of life and mental health. The trial registration was carried out in the Brazil Clinical Trials Registry (RBR-5qh6f3v), https://ensaiosclinicos.gov.br/rg/RBR-5qh6f3v .